A non toxic natural food colorant and antioxidant 'Peonidin' as a pH indicator: A TDDFT analysis. (October 2018) - Rajan, Vijisha K.; T.K., Shameera Ahamed; C.K., Hasna; Muraleedharan, K.
Graphical abstract: Highlights: In acidic media Peonidin is in its cationic form and gives purple color to flowers. In alkaline media Peonidin is in its base form giving blue color to flowers. Peonidin to act as efficient pH indicator besides its radical scavenging capacity. Peonidin is non irritant, non mutagenic and non tumerogenic. Abstract: A computational inestigation on the difference in colors of two plants 'Peony' and 'Morning glory' by the same pigment 'Peonidin' has been performed by means of absorption characteristics. Peonidin imparts purple color to the flowers in Peony and blue to that in Morning glory. TDDFT tool in Gaussian 09 software package has been employed to analyze the UV–vis spectra and has shown that in acidic media Peonidin exists in its flavylium cationic form where as in alkaline media it exists in the quinoidal base form. These two structural forms have colors red and blue respectively. TDDFT results of flavylium ion in acetic acid moves the absorption to higher wavelength and corresponds to purple color and is the color of Peony flower. One of the quinoidal bases in alkaline media gives violet-blue color to flowers in Morning glory. This is true as Peony grows in acidic soil only while Morning glory grows in alkaline soil only. The affinity towards pH values makes Peonidin to act as pH indicator besides its radical scavenging capacity. Further a good food colorant must be non toxic. The toxicological analysis has shown that Peonidin is non-irritant, non-mutagenic, non-carcinogenic and non-tumorigenic. The compound has sufficient solubility to use as a potential drug. Also the compound has a positive drug score. All these results confirm the potential druggability of Peonidin and its non toxicity.